Cytomegalovirus Antibody Elevation in Bipolar Disorder: Relation to Elevated Mood States - A. R. Prossin; R. H. Yolken; M. Kamali; M. M. Heitzeg; J. B. Kaplow; W. H. Coryell; M. G. McInnis (Neural Plasticity)
The neurobiology of mood states is complicated by exposure to everyday stressors (e.g., psychosocial, ubiquitous environmental infections like CMV), each fluctuating between latency and reactivation. CMV reactivation induces proinflammatory cytokines (e.g., TNF-α) associated with induction of neurotoxic metabolites and the presence of mood states in bipolar disorder (BD). Whether CMV reactivation is associated with bipolar diagnoses (trait) or specific mood states is unclear. We investigated 139 BD type I and 99 healthy controls to determine if concentrations of IgG antibodies to Herpesviridae (e.g., CMV, HSV-1, and HSV-2) were associated with BD-I diagnosis and specific mood states. We found higher CMV antibody concentration in BD-I than in healthy controls (T234=3.1, Puncorr=0.002; Pcorr=0.006) but no difference in HSV-1 (P>0.10) or HSV-2 (P>0.10). Compared to euthymic BD-I volunteers, CMV IgG was higher in BD-I volunteers with elevated moods (P<0.03) but not different in depressed moods (P>0.10). While relationships presented between BD-I diagnosis, mood states, and CMV antibodies are encouraging, they are limited by the study’s cross sectional nature. Nevertheless, further testing is warranted to replicate findings and determine whether reactivation of CMV infection exacerbates elevated mood states in BD-I.